RANCANG BANGUN SISTEM MONITORING KUALITAS AIR UNTUK PEMBUDIDAYAAN IKAN PATIN BERBASIS INTERNET OF THINGS (IOT) - Willy Susanto; Gede Sukadarmika; Widyadi Setiawan (Jurnal SPEKTRUM, 2021)
The design of this device will help people who want to cultivate the pangas catfish by monitoring water quality based on predetermined parameters. This water quality monitoring system device will carry out water quality readings for the farming with temperature sensor, pH sensor, and turbidity sensor. The results which gained from the sensors will be processed by NodeMCU that is used for the microcontroller. The final results of the data obtained will be processed by the microcontroller NodeMCU and will be sent to the IP Address which is supplied by the provider and will be displayed by the device that had been connected to the IP Address provided. From the results of the overall tool testing, this system can work well, thus it can detect good water quality and warning water quality for pangas catfish farming and also send the data to the web server through web browser’s application in both smartphones or laptop/pcs if the quality of the water in a “good” (save) or “warning” condition.